(untitled) (Journal of Comparative & International Higher Education, 2024)
This in-depth qualitative study investigated how international students experienced academic, psychological and sociocultural adjustment during the COVID-19 pandemic. Whilst a burgeoning body of research examines the impact of the coronavirus pandemic on international students, few studies foreground students’ lived experiences. This study gathered data through semi-structured interviews with 30 international postgraduate students who undertook degree programs at British universities in 20-21. A thematic analysis revealed that COVID-19-related stressors negatively impacted students’ psychological adjustment and led to a sense of isolation and detachment from the host environment, with students reporting difficulties in instigating and maintaining social ties. Experiences of academic adjustment were nuanced, with findings suggesting that the pandemic acted as either a barrier or facilitator of adjustment, depending on the students’ personal circumstances. With global epidemics increasingly likely, the findings from this study can support higher education institutions in developing institutional policies on how to support their international students in times of global health crises.